Country Risk Evaluation Methods and Applications - Kosmidou, Kyriaki; Doumpos, Michael; Zopounidis, Constantin (Springer Optimization and Its Applications, 2008)
Financial globalization has increased the significance of methods used in the evaluation of country risk, one of the major research topics in economics and finance. Written by experts in the fields of multicriteria methodology, credit risk assessment, operations research, and financial management, this book develops a comprehensive framework for evaluating models based on several classification techniques that emerge from different theoretical directions. This book compares different statistical and data mining techniques, noting the advantages of each method, and introduces new multicriteria methodologies that are important to country risk modeling. Key topics include: A review of country risk definitions and an overview of the most recent tools in country risk management In-depth analysis of statistical, econometric and non-parametric classification techniques Several real-world applications of the methodologies described throughout the text Future research directions for country risk assessment problems This work is a useful toolkit for economists, financial managers, bank managers, operations researchers, management scientists, and risk analysts. Moreover, the book can also be used as a supplementary text for graduate courses in finance and financial risk management.